Association Between Peripheral Adiponectin and Lipids Levels and the Therapeutic Response to Donepezil Treatment in Han Chinese Patients With Alzheimer’s Disease - Wan, Lili; Lu, Jin; Huang, Jinlu; Huo, Yan; Jiang, Shan; Guo, Cheng (Frontiers in Aging Neuroscience, 2020)
Acetylcholinesterase inhibitors (AchEIs) including donepezil (DNP) are considered to be the most important Acetylcholinesterase inhibitors (AChEIs) including donepezil (DNP) are considered to be the most promising therapeutic possibilities of Alzheimer’s Disease (AD). The response to DNP in AD patients varies and itis valuable to identify the potential markers that can predict the efficacy. Moreover, DNP has been found to affect on bone function but the exact mechanism is still unclear. Lipids and adipokine may link to AD and DNP directly or indirectly and might be potential biomarkers or therapeutic drug targets. This study was aimed at investigating the relationships among adiponectin (APN), lipids levels and the response to DNP, and to identify whether the effect of DNP in AD treatment is related to its effect on the level of APN in systemic circulation. The study recruited 85 AD patients with DNP treatment, of which 47 DNP responders and 38 DNP non-responders. Mini-Mental State Examination was performed to evaluate the memory impairment. Plasma APN was measured with ELISA. The genotypes of single nucleotide polymorphisms rs1501299 and rs22417661 in APN for each patient were identiﬁed. Plasma lipids were quantified with gas chromatography coupled mass spectrometry. Correlations among APN, lipid metabolomics and DNP responded were evaluated. APN was significantly decreased in DNP responders. Methyl stearate and glycerol-3-phosphate, used for characterizing adipogenic differentiation, was significantly decreased in DNP responders compared to DNP non-responders. APN and small molecule lipid can be used as potential biomarkers to evaluate the efficacy of DNP. The results of metabolomics indicated that there was no change in the metabolic pathway of fatty acid metabolism and glucose metabolism in DNP responders, suggesting that APN-related biological function did not decrease in DNP responders. Our result suggests that more attention should be pay to the sources and biological functions of APN in AD with DNP treatment.